My kind of Christmas [large type] - Dailey, Janet (Center Point Large Print, 2018)
"Branding Iron, Texas, is Travis Morgan's last resort, and the abandoned ranch he inherited isn't much more welcoming than the prison where he spent the last three years doing time for a tragic accident. Travis finds celebrating Christmas is the last thing on his mind until he meets the town's sweetly stubborn mayor, Maggie Delaney"--